Potential for the Bio-Detoxification of the Mycotoxins Enniatin B and Deoxynivalenol by Lactic Acid Bacteria and Bacillus spp. - Sandra Mischler; Amandine André; Irene Chetschik; Susanne Miescher Schwenninger (Microorganisms)
Mycotoxins, toxic compounds produced by fungi, pose significant risks to food safety and human health. This study investigates the bio-detoxification potential of 238 strains of lactic acid bacteria (LAB) and Bacillus spp., previously isolated from cereals (including mycotoxin-contaminated grains), against the emerging mycotoxin, enniatin B (ENB), and the prevalent mycotoxin, deoxynivalenol (DON). Out of the tested strains, 26 demonstrated notable mycotoxin reduction capabilities, including 2 Bacillus pumilus and 24 Bacillus licheniformis strains. B. licheniformis strains MA572, MA695, MA696, TR174a, TR284, TR363, and TR466a degraded ENB to levels below the detection limit, and six strains reduced DON by 30–35%; B. licheniformis TR251b and TR374 showed the highest DON reduction with 35.7%. The most promising strains for bio-detoxification were B. licheniformis TR284, which achieved a 100% reduction in ENB and a 28.6% reduction in DON and B. licheniformis TR388 with a 97.5% reduction in ENB and a 31.9% reduction in DON. None of the tested LAB strains significantly reduced either mycotoxin. These findings highlight the promising potential of B. licheniformis strains in bio-detoxifying mycotoxin-contaminated cereal products. Further research into the underlying detoxification mechanisms and safety aspects is essential to develop effective bio-detoxification strategies for enhancing food safety.